Ukama Ustawi CGIAR Food Systems Accelerator Technical Report (Concept Note) - Ng'anga, Salome; Karimi, Peter; Zulu-Hume, Mercy F.; Dahl, Hauke; Nkosi, Mahlatse (CGIAR System Organization, 2022)
One of the major underlying reasons for poor agricultural performance in East and Southern Africa (ESA) is the low efficiency of agricultural value chains and lack of resilience against climate shocks. Many agricultural value chains are fragmented and characterized by instability of relationships between off-takers and smallholder and emerging farmers. The ones that suffer the most from these inefficiencies and threats are the farmers. There are significant hurdles to farmers and market systems. These include access to affordable inputs, advisories, logistics, finance, and market linkages. Agribusinesses are addressing these challenges through their products and services, and supporting farmers to improve productivity, incomes, and resilience to climate change. This is particularly important in East and Southern Africa, where farmers are engaged in maize production which is vulnerable to climate change and projected to face not only 15% climate-related declines in yield without adaptation, but also challenges from diminished cropland suitability and poor agronomic inputs and management; degraded environmental bases with declining soil fertility and degraded water systems.